Comprehensive subgroup analyses of survival outcomes between clear cell renal cell adenocarcinoma and papillary renal cell adenocarcinoma. (3rd November 2020) - Huang, Jingyi; Huang, Da; Yan, Jiaqi; Chen, Tianhe; Gao, Yi; Xu, Danfeng; Na, Rong
Abstract: To comprehensively compare the survival outcomes of clear cell renal cell carcinoma (ccRCC) and papillary renal cell carcinoma (pRCC), the study cohort included ccRCC and pRCC patients in 2004–2017 from the Surveillance, Epidemiology, and End Results (SEER) database, which comprises 18 registries. Primary outcomes including overall mortality (OM) and cancer‐specific mortality (CSM) were evaluated. Subgroup analyses were conducted for different ages, race, and disease stages. A total of 112, 270 cases were eligible for the current analysis, including 92, 209 cases of ccRCC and 20, 061 cases of pRCC. Univariate analyses suggested that pRCC has a more favorable outcome than ccRCC in terms of CSM (HR: 0.72, 95% CI: 0.68–0.75, p  < 0.001) and OM (HR: 0.90, 95% CI: 0.88–0.93, p  < 0.001). Multivariate‐adjusted HRs suggested that pRCC has worse survival outcomes than ccRCC (adjusted HR: 1.08 for CSM and 1.05 for OM, both p  < 0.05). Subgroup analyses showed that pRCC had a significantly poorer prognosis than ccRCC among patients ≤45 years old (HRCSM : 1.59, 95% CI: 1.31–1.93, p  < 0.001; HROM : 1.63, 95% CI: 1.40–1.90, p  < 0.001). Among patients with distant metastasis, those with pRCC had a higher risk of CSM and OM than those with ccRCC (HRCSM : 1.28, 95% CI: 1.19–1.39, p  < 0.001; HROM : 1.30, 95% CI: 1.21–1.40, p  < 0.001). Propensity score analyses for patients ≤45 years old and those with metastasis showed similar results. The lack of information on pRCC subtypes in the SEER database was a limitation. In conclusion, pRCC has poorer survival outcomes than ccRCC among patients younger than 45 years old and patients with distant metastasis. Abstract : Prognosis of pRCC is commonly more favorable than that of ccRCC. But, for patients less than 45 years old and patients with metastatic RCC, the survival outcome of pRCC is worse contrarily.